Birth Education Programme for expectant father: Qualitative Study on Needs Assessment - Zainab, Mohd Shafie; Rohani, Ismail (2016)
Introduction, Government hospital allowed husbands to be with their wives during in labour, but unfortunately they do not know what to do and panic during the labour process. So, birth education programme will be the way to provide them some knowledge and what to do during the stage and be an active birth partner as well. Objectives, The general objective of this study is to explore the needs of birth education programme for expectant father. Background, this new birth education programme is meant for expectant father, this programme will prepare them to be an active birth partner during childbirth. Support and active assistant from husband also promote a natural birth. Method, it is a qualitative study, which focuses on focus group discussion. Three focus group discussion is divided into husbands, wives and nurses groups, and 32 participants selection is based on convenience purposively sampling from six health center of Kuala Terengganu region. Open ended questions guideline were used to explore the needs of expectant father, and data was transcribed according identified themes. Findings, the identified themes are knowledge on pregnancy & birth, is about pregnancy, care during pregnancy, the process of labour, treatment and intervention during labour, care during labour, husbands attitude, is about roles and responsibilities, and practice during assist their wives, is about methods to reduce pain and anxiety during labour. Conclusions, All participant agreed that husbands need to involved in birth education programme. Support from husband is important during labour and this programme is helping husbands to be a birth partner for their wives.